2018
DOI: 10.1007/s10792-018-0948-5
|View full text |Cite
|
Sign up to set email alerts
|

Giraffe or leopard spot chorioretinopathy as an outstanding finding: case report and literature review

Abstract: Leopard spot retinopathy is an uncommon but clinically distinct manifestation of various disorders. BDUMP may present with leopard spot retinopathy, anterior uveal tract involvement and neovascular glaucoma. As EDI-OCT showed involvement and increased thickening of choroid in both cases of BDUMP and IUES, it may be better to consider such cases as leopard chorioretinopathy and categorize these entities as a member of pachychoroid pigment retinopathy disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Harada et al [ 5 ] reported UES in a 41-year-old man with a marked choroidal thickening of 787 μm on spectral domain OCT and low reflection of the outer choroidal layer, and pointed out that an increase in choroidal thickness may be related to the onset of UES. Jabbarpoor Bonyadi et al [ 6 ] reported a case of idiopathic UES with bullous non-rhegmatogenous RD associated with leopard spot retinopathy. Since the OCT findings in that study revealed subfoveal choroidal thickening, they speculated that it may be categorized as pachychoroid spectrum disease.…”
Section: Discussionmentioning
confidence: 99%
“…Harada et al [ 5 ] reported UES in a 41-year-old man with a marked choroidal thickening of 787 μm on spectral domain OCT and low reflection of the outer choroidal layer, and pointed out that an increase in choroidal thickness may be related to the onset of UES. Jabbarpoor Bonyadi et al [ 6 ] reported a case of idiopathic UES with bullous non-rhegmatogenous RD associated with leopard spot retinopathy. Since the OCT findings in that study revealed subfoveal choroidal thickening, they speculated that it may be categorized as pachychoroid spectrum disease.…”
Section: Discussionmentioning
confidence: 99%
“…In our series, there were no instances of prominent drusen or clumping of retinal pigment epithelium on the surface of the lesion, no cases with prominent clumps of orange pigment or serous subretinal fluid associated with the flat melanocytic choroidal lesion, and no instances of giraffe or leopard spot chorioretinopathy [ 34 ] in the affected eyes. Finding of any of these features should suggest a diagnosis other than isolated choroidal melanocytosis.…”
Section: Discussionmentioning
confidence: 77%
“…This disorder is an acquired paraneoplastic stimulation of uveal melanocytes related to an underlying non-melanoma systemic malignant neoplasm (usually a carcinoma) [ 31 ]. The characteristic ocular features of this disorder are relatively rapid onset, bilaterality in almost all cases, diffuse proliferation of uveal melanocytes in the affected eyes, and an unusual associated pattern of giraffe or leopard spot chorioretinopathy [ 34 ]. In many cases, there is accentuated multifocal proliferation of melanocytes rather than uniform stimulation of all uveal melanocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic central serous chorioretinopathy (CSCR), commonly noticed in young males with a Type A personality being treated with high doses of corticosteroids, is characterized by a leopard-spot appearance on fundoscopy due to formed subretinal yellowish material in areas of chronic or recurrent neurosensory detachment. 10 Other systemic and ophthalmic diseases that would present with this fundoscopic pattern are large B-cell vitreoretinal lymphoma (VRL), 11 uveal effusion syndrome, 12 lymphocytic leukemia, 13 bilateral diffuse uveal melanocytic proliferation (BDUMP) 14 and hypertensive choroidopathy. 15 …”
Section: Discussionmentioning
confidence: 99%